D9.2 Communication Action Plan (RP3) - Papoutsa, Christiana; Prodromou, Maria; Tziortzis, Stelios; Komodromos, George (My University, 2022)
This deliverable reports on the Communication Action Plan for the project EXCELSIOR, as established in Deliverable D9.1. It provides an update on the overall progress implemented related to the Communication Action Plan up to M32. Furthermore, it provides an update in relation to the activities, such as dissemination events and outreach activities, of the ECoE for RP1 and RP2 mentioning the impact and audience reached though the specific activities. Finally, the possible future activities in terms of number of events that are scheduled to be planned for the period M32 to M70 are presented. The present document constitutes an update of the ‘Communication Action Plan’ in the framework of the EXCELSIOR project, dedicated to Task 9.1 ‘Communication strategy and action plan’ under the work package WP9 ‘Communication, Engagement and Networking’. D9.2 is delivered on Month 32 of the project and focuses on the first 32 months of the project, up to the first and second reporting period of the project. This document will be updated one more time in Month 70 of the project
Keywords: Remote Sensing; EXCELSIOR; ERATOSTHENES Centre of Excellence; Earth Observation